Effectiveness of short vs. long-distance sprint training on sprinting and agility performance in young soccer players - Rey, Ezequiel; Carrera, Samuel; Padrón-Cabo, Alexis; Costa, Pablo B. (Biology of Sport, 2024)
The purpose of this study was to examine the effects of short sprint-distance training (SST) compared with long sprint-distance training (LST), matched for the total session training volume, on short-, medium- and long-distance sprint performance and agility in young soccer players. Eighteen U19 male players (age: 17.1±0.7 years; height: 178.0±6.3 cm, body mass: 69.4±6.6 kg) were randomly assigned to SST ( n = 9) or LST ( n = 9) group. The intervention programs were performed 2 times a week over 6 weeks. Before and after training period, 5 m, 10 m, 20 m, 30 m and 40 m sprint, and agility were assessed. Within-group analysis showed significant improvements ( p ≤ 0.001) in 5 m, 10 m, 20 m, 30 m and 40 m sprint from pretest to posttest in SST (9.2%, 6.6%, 5.3%, 2.9%, and 2.5%, respectively) and LST (10.5%, 8.5%, 6.5%, 5.1%, and 4.7%, respectively). Players in both SST and LST also showed significant enhancements in agility from pretest to posttest. In the between-groups analysis, there were no differences between the sprint training groups (SST vs. LST) in any variable ( p > 0.05). In conclusion, the findings of this study indicate that both sprint training distances used seem to be effective to improve soccer-specific performance measures. However, due to the better percentage changes obtained by LST group in all fitness variables, this method could be considered as preferred method.